PENEGAKAN HUKUM TERHADAP PELAKU TINDAK PIDANA PENCUCIAN UANG PADA ASURANSI (STUDI PUTUSAN No.740/PID.SUS/2014/PT.MDN) - Aulia Annisa; Bismar Nasution; Sunarmi Sunarmi; Mahmud Mulyadi (Universitas Sumatera Utara, 2019)
ABSTRACT The perpetrators of the crime of money laundering in insurance companies using mode-advanced mode so difficult are examined. Money laundering is a criminal offence that are attributable with other criminal acts. Origin of the crime (predicate crime) in accordance with article two (2) paragraph one (1) Law No. 8 year 2010. After he had done the crime perpetrator then origin such criminal conduct placement (placement) for the criminal offence of money results not known that result from criminal acts. The perpetrators of the obscure origin of these funds by placing in the insurance company up to with a specific time limit. The perpetrator put money into the insurance company and take the results of the Fund. The money like they not halal money of any crime. This is where the perpetrators of money laundering was very interested to do money laundering from insurance. Defendant Maria Rina Chrsissanty Sinaga has earned or gained control of placement, transferring, payments, grants, donations, day care, or to use the Treasures that he knew or should she bargained for was the result of a criminal act counterfeiting and forgery of the transfer to the account of such customer without the knowledge of its customers to conceal and disguise the proceeds of criminal acts. The process of proof in the criminal offence of money laundering through the insurance in the case of Maria Rina Chrissanty Sinaga using theories based on positive law because the system is adhered to the teaching that is based on whether or not the defendant is guilty there lack of valid evidence tools according to laws that can be used to prove the fault of the defendant. Judges here see anything presented by prosecutors with the tools themselves and then drop the verdict in accordance with kajahatan the accused. In its ruling No. 740/PID. SUS/2014/PT. MDN defendant in the snare of article 3 of law No. 8 Year imprisonment punishment 2010 with 2 (two) year 6 (six) months and a fine of Rp. 100.000.000 (one hundred million rupiah) if the fine is not paid then replaced with sentence 1 (one) months imprisonment. Keywords: Crime, Money Laundering, Insurance